2019
DOI: 10.3389/fpls.2019.00781
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Jasmonate-Induced Changes of Flavor Profiles During the Processing of Green, Oolong, and Black Tea

Abstract: Tea aroma is one of the most important factors affecting the character and quality of tea. Here we describe the practical application of methyl jasmonate (MeJA) to improve the aroma quality of teas. The changes of selected metabolites during crucial tea processing steps, namely, withering, fixing and rolling, and fermentation, were analyzed. MeJA treatment of tea leaves (12, 24, 48, and 168 h) greatly promotes the aroma quality of green, oolong, and black tea products when comparing with untreated ones (0 h) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…According to our previous results, the application of MeJA to fresh tea leaves significantly enhanced the aroma quality of prepared teas 26 . Previously, we conducted combined transcriptomic and volatile metabolite analyses and partially elucidated physiological changes at the molecular level 27 .…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…According to our previous results, the application of MeJA to fresh tea leaves significantly enhanced the aroma quality of prepared teas 26 . Previously, we conducted combined transcriptomic and volatile metabolite analyses and partially elucidated physiological changes at the molecular level 27 .…”
Section: Introductionsupporting
confidence: 53%
“…This phenomenon is caused by the induction of key LOX enzymes due to MeJA priming mimicking herbivorous insects 1 and is commonly activated by jasmonate-dependent defense mechanisms. This timely response triggers the formation of fatty acid-derived volatiles in fresh tea leaves, which are eventually stored as glycosides and in turn improve the sensory properties of tea products 26 . Hence, MeJA priming could be used to activate defense mechanisms and reduce the amount of pesticide used during tea farming.…”
Section: Discussionmentioning
confidence: 99%
“…To a large extent, aroma determines the price of tea products. Exogenous jasmonic acid spraying can effectively increase the alcohol and hexenyl ester contents in oolong tea and thus improve the tea quality 24 . In this study, we identified 13 CsJAZ genes based on the tea plant draft genome sequence (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The substantial enhancement in carbohydrate levels might also be due to the activation of photosynthetic machinery of stressed plants. In a recent study, researchers found that the application of methyl jasmonate improved the contents of different carbohydrate metabolites such as benzyl alcohol, phenyalacetaldehyde, benzaldehyde, 2-phenylethyl alcohol, and trans-2-hexanal in tea plants ( Camellia sinensis ) [285]. Ahmadi et al [286] found that exogenously applied methyl jasmonate under salt stress modulated the salinity induced peroxidation through increased levels of soluble sugar in Brassica napus leaves.…”
Section: Role Of Jasmonates In Regulation Of Osmolytes Under Abiotmentioning
confidence: 99%